The meaning of out-of-field teaching for educational leadership. Issue 1 (2nd January 2017) - du Plessis, Anna E.; Carroll, Annemaree; Gillies, Robyn M.
Abstract : Assigning teachers to a position for which they are not suitably qualified influences effective educational leadership. The paper reveals assumptions and misconceptions about the lived experiences of teachers in out-of-field positions and what it means for effective educational leadership. The multilayered meaning of out-of-field teaching for quality education is an international concern which includes countries such as Australia, USA, UK, Korea, Europe, Turkey and South Africa. The paper reports on a transnational qualitative investigation conducted in Australia and South Africa at seven schools in different educational environments. The meaning of lived experiences in relation to out-of-field teaching and educational leadership is explored through the lenses of educational directors, principals, specialist and out-of-field teachers and parents. An in-depth discussion of the practical and social implications unveils taken-for-granted traditions and cultures in relation to out-of-field teaching. The paper concludes with an in-depth discussion of the meaning out-of-field teaching has for educational leadership, while it underlines specific complexities for decision-making and policy development. The need for further research in relation to educational leadership training and professional development in relation to the out-of-field situation is revealed.